Research Needs and Logistic Impediments in Restoration, Enhancement, and Management Projects: A Survey of Land Managers - Carrie R. Adams; Nancy M. Steigerwalt (EDIS)
ENH1161, a 7-page report by Carrie R. Adams and Nancy M. Steigerwalt, presents the results of a survey of practitioners and land managers to determine research and outreach needs for restoration, enhancement, and management goals in the southeastern coastal plain. Includes references. Published by the UF Department of Environmental Horticulture, March 2010.